Meningkatkan kemampuan mengenal huruf bagi peserta didik slow learner menggunakan media assembler edu : Single Subject Research di Kelas IV SDN 10 Sungai Sapih - Mutia Ningsih; Syari Yuliana; Zulmiyetri; Arisul Mahdi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This article discusses efforts to improve letter recognition skills using the Assemblr Edu medium for slow learner students. Slow learners often face obstacles in recognizing letters due to limitations in memory, thinking speed, and difficulties in processing learning materials. These conditions affect students’ reading and writing abilities. Based on assessments conducted at SDN 10 Sungai Sapih, it was found that the letter recognition ability of slow learner students was still low, particularly in distinguishing and naming alphabet letters. Therefore, this study aims to improve letter recognition skills among slow learner students through the use of Assemblr Edu, an interactive learning medium based on augmented reality technology that is engaging and easy to use. This research employed a quantitative approach using the Single Subject Research (SSR) experimental method with an A–B design. The research subject was a fourth-grade slow learner student at SDN 10 Sungai Sapih. Phase A (baseline) was used to measure the student’s initial ability to recognize letters before the intervention, while Phase B (intervention) involved learning activities using Assemblr Edu. Data were collected through oral and performance tests and analyzed using visual graphic analysis techniques to observe changes in ability from Phase A to Phase B. The results showed an improvement in students’ ability to recognize letters after the intervention using Assemblr Edu. Students became more capable of identifying the shape and sound of letters, showed better focus, and demonstrated greater enthusiasm in learning. Thus, it can be concluded that Assemblr Edu is effective in improving letter recognition skills among slow learner students, as it provides concrete, engaging, and interactive learning experiences suited to their learning characteristics.